Enhanced joint pain in diabetic patients with knee osteoarthritis is associated with increased synovitis, synovial immune cell infiltration, and erythrocyte extravasation - Eitner, Annett; Rutte, Veronika; Marintschev, Ivan; Hofmann, Gunther O.; Schaible, Hans-Georg (Frontiers in Endocrinology, 2024)
Objective: Diabetes mellitus (DM) is an important risk factor for the development of osteoarthritis (OA), increasing OA progression and OA pain. To gain insight into the underlying mechanisms of how DM exacerbates OA processes and OA pain, this study analyzed histological differences of synovial tissues from non-DM and DM patients with OA and correlated these differences with knee pain severity. Materials and methods: Synovial tissue was obtained from 12 non-DM and 10 DM patients with advanced knee OA who underwent total knee arthroplasty. Synovial inflammation was assessed using the Synovitis score developed by Krenn. The Knee Injury and Osteoarthritis Outcome Score (KOOS) was used to assess knee pain intensity and disability in OA patients. The number of mast cells, macrophages, nerve fibers, capillaries, larger vessels and erythrocyte extravasation were analyzed microscopically in histological and immunostained synovial sections from non-DM and DM patients. Association analyses were performed to determine associations between OA knee pain and synovial changes affected by DM. Results: Synovial tissue from OA patients with DM had a higher synovitis score, more erythrocyte extravasation, and contained higher numbers of mast cells and macrophages compared to non-DM patients. The number of capillaries and vessels in the lining/sublining layer of the synovial tissue was reduced in DM patients. OA patients with DM had more severe knee pain compared to non-DM patients. The KOOS pain score was associated with the synovitis score, the number of tissue macrophages, and the number of mast cells in the synovial tissue (adjusted for age, sex, and BMI). In addition, the erythrocyte extravasation score was associated with the KOOS pain score and with the synovitis score.The study suggests that increased OA progression and pain severity in patients with DM result from more pronounced synovitis and synovial vascular leakage and increased infiltration of macrophages and mast cells.